Structures of proteases for ubiqutin and ubiquitin-like modifiers - Ha, Byung Hak; Kim, Eunice EunKyeong (KOREAN SOCIETY BIOCHEMISTRY & MOLECULAR BIOLOGY, 2008)
Post-translational modifiers can alter the function of proteins in many different ways. The conjugation of ubiquitin (Ub) and ubiqutin-like modifiers (Ubls) to proteins has been shown to be especially crucial in regulating a variety of cellular processes including the cell cycle, growth control, quality control, localization and many more. It is a highly dynamic process and involves a number of enzymes called Ell, E2 and E3. Ub and Ubls are removed from the target proteins by deubiquitinating enzymes (DUBs) or Ubl-specific proteases (ULPs), thereby deconjugation can act as an additional level of control over the ubiquitin-conjugation system. In addition, DUBs and ULPs are responsible for activating Ub and Ubls from their inactive corresponding precursor forms. Here we review recent progress in molecular details of these deconjugating enzymes of Ubls.
Keywords: CRYSTAL-STRUCTURE; DEUBIQUITINATING ENZYME; CONJUGATING ENZYME; NEDD8 CONJUGATION; CYSTEINE PROTEASE; HUMAN ATG4B; SUMO; DOMAIN; PROTEINS; COMPLEX